“Under the Lebanese flag”: National Unity in the Movement of October 17th - Rakickaja, Marija (Politologija, 2021)
This article aims to understand how national unity is being constructed in the context of the protest movement, started on October 17th, 2019 in Lebanon, what it is grounded on and what is the role of the elite in the process. The study is based on an ethnographic research conducted in Beirut between October 17th and December 19th, 2019, and analyzes the movement of October 17th as an instance of nation-building from below.It became clear that a unity across different communities has emerged from below and reached “tipping point” coinciding with the movement of October 17th, which provided new spaces for people to engage in “viral peer-to-peer networking” creating a “feedback loop” reinforcing the unity based on shared grievances and idea of a civil state. It is argued that elite is not necessary for a national sentiment to emerge. Its durability is though assumed to be related to efficacy and thus possibly impacted by leadership.
Keywords: Lebanon; nationalism; social movements; sectarianism; confessionalism